Revisiting current "barefoot doctors" in border areas of China: system of services, financial issue and clinical practice prior to introducing integrated management of childhood illness (IMCI) - Li Xiuyun; Chongsuvivatwong Virasakdi; Xia Xiaoling; Sangsupawanich Pasuree; Zheng Wenjing; Ma Keling (BMC, 2012)
Abstract Background Under-5-years child mortality remains high in rural China. Integrated management of childhood illness (IMCI) was introduced to China in 1998, but only a few rural areas have been included. This study aimed at assessing the current situation of the health system of rural health care and evaluating the clinical competency of village doctors in management of childhood illnesses prior to implementing IMCI programme in remote border rural areas. Methods The study was carried out in the border areas of Puer prefecture of Yunnan province. There were 182 village doctors in the list of the health bureau in these border areas. Of these, 154 (84.6%) were recruited into the study. The local health system components were investigated using a qualitative approach and analyzed with triangulation of information from different sources. The clinical component was assessed objectively and quantitatively presented using descriptive statistics. Results The study found that the New Rural Cooperative Medical Scheme (NRCMS) coordinated the health insurance system and the provider service through 3 tiers: village doctor, township and county hospitals. The 30 RMB per person per year premium did not cover the referral cost, and thereby decreased the number of referrals. In contrast to available treatment facilities and drug supply, the level of basic medical education of village doctors and township doctors was low. Discontent among village doctors was common, especially concerning low rates of return from the service, exceptions being procedures such as injections, which in fact may create moral hazards to the patients. Direct observation on the assessment and management of paediatric patients by village doctors revealed inadequate history taking and physical examination, inability to detect potentially serious complications, overprescription of injection and antibiotics, and underprescription of oral rehydration salts and poor quality of counseling. Conclusion There is a need to improve health finance and clinical competency of the village doctors in the study area.